Friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite
Through the friction deposition additive manufacturing method, the complex structure manufacturing and corrosion resistance of continuous fiber mesh reinforced metal-based composite materials are solved, and high-performance metal-based composite materials are realized, avoiding the excessive interfacial reaction caused by melting and re-solidation. , improves the overall performance and corrosion resistance of the material.
Patent Information
- Application Number
- CN202411382786.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing continuous fiber mesh reinforced metal matrix composite manufacturing methods have problems such as difficult to manufacture complex structures, excessive interface reactions and corrosion resistance, especially the brittle phase generation and corrosion potential difference caused by metallurgical reactions at high temperatures are difficult to effectively regulate. .
Using friction deposition additive manufacturing method, the cleanup and electrochemical woven surface of the continuous fiber mesh, combined with the introduction of corrosion inhibitors, realize layer-by-layer stacking of pure solid phase processes, avoid melting and re-solidation, and improve mechanical interlocking and resistance. Corrosive.
It realizes reliable manufacturing of complex structures, avoids excessive interface reaction, significantly improves the overall load-bearing and corrosion resistance of composite materials, and has low production costs, and is suitable for a variety of high-performance manufacturing.
Smart Images

Figure CN119260312A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a friction deposition additive manufacturing method for a metal-based composite material, and belongs to the technical field of metal-based composite materials. Background Art
[0002] With the advancement of modern engineering technology, traditional alloy materials are difficult to meet the requirements of reliable use in extreme service environments. For example, in order to meet the complex situations such as impact and collision faced by wheeled extraterrestrial exploration vehicles when serving on various unknown surfaces without being damaged, their wheels must meet the requirements of high strength, impact resistance, wear resistance, corrosion resistance, etc. It is difficult for traditional materials to meet this series of complex working conditions at the same time. As a new type of composite material system, continuous fiber grid reinforced metal matrix composites will bear most of the external load when subjected to external loads, and the main function of the matrix is to transfer and redistribute the load. The mechanical properties of composite materials will be affected by the fiber properties, the matrix properties and the interface bonding strength between the two, and are also related to the weaving method and direction of the fiber grid. For this type of composite material, its fibers mainly include three types of toughening mechanisms: (1) Fiber bridging: its essence is a crack tail effect, that is, when the two surfaces near the bridging fiber connect the fiber tip, a force is provided to the crack surface to make the cracks approach each other, which prevents the further expansion of the crack and has a strengthening effect; (2) Crack bending and deflection: when the crack extends to the fiber, the crack extension path is bent and deflected, thereby increasing the total surface area of the crack and the total energy absorbed, which has a toughening effect; (3) Fiber desorption: when the interface between the fiber and the matrix is peeled off under the action of external force, the fiber and the matrix are peeled off at the interface, and the fiber debonding effect occurs, which consumes a lot of energy and further improves the toughness of the composite material. Combining the above three points, continuous fiber grid reinforced metal matrix composites can be said to have a breakthrough application potential in the application of high-strength and high-toughness structural materials.
[0003] However, the preparation of this type of material currently faces the following difficulties: (1) Complex structures are difficult to manufacture: Existing continuous fiber mesh reinforced metal matrix composites are usually prepared by melt infiltration / pressure infiltration or hot pressing sintering of continuous fiber mesh preforms, which means that their structural form is relatively limited and can only manufacture some simple geometric structures. At the same time, considering the structural characteristics of the continuous fiber mesh, machining a complex structure from a simple geometric structure directly faces the problem of destroying the continuity of the fiber; (2) Excessive interface reaction: The molten matrix material is very likely to undergo metallurgical reaction with the continuous fiber mesh at high temperature, generating excessive and thick compounds, such as Fe2Al5, Fe4Al 13, Al4C3 and other brittle or easily hydrolyzed phases, which have a very negative impact on the overall load-bearing performance and corrosion resistance of the composite material; (3) Corrosion resistance is difficult to guarantee: Due to the different materials between the matrix and the fiber, there is inevitably a corrosion potential difference in nature, resulting in poor corrosion resistance. However, due to the high temperature characteristics of traditional manufacturing methods, most corrosion protection methods cannot be applied in the manufacturing process, which makes this poor corrosion resistance difficult to effectively control. In view of the above problems, it can be known that the essential means to break through the difficulty of manufacturing continuous fiber grid reinforced composite materials is to avoid melting and resolidification forming and realize additive manufacturing mode, because, if an additive manufacturing method based on the principle of solid phase deposition can be proposed, it will be expected to achieve a revolutionary breakthrough in the reliable manufacturing of continuous fiber grid reinforced metal matrix composites. Summary of the invention
[0004] The present invention aims to solve the problems of difficult manufacturing of complex structures, excessive interface reaction and difficult to ensure corrosion resistance in existing continuous fiber grid reinforced metal matrix composite material manufacturing methods, and further proposes a friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite materials.
[0005] The technical solution adopted by the present invention to solve the above problems is: the steps of the present invention specifically include:
[0006] Step 1, continuous fiber mesh surface cleaning: cleaning the continuous fiber mesh surface, including degreasing, pickling and weak etching;
[0007] Step 2, surface texturing of the continuous fiber mesh: the surface of the continuous fiber mesh is electrochemically texturized by a pulse electrodeposition process to produce a high-roughness surface structure and simultaneously introduce a corrosion inhibitor to strengthen the mechanical interlocking effect between the continuous fiber mesh and the matrix, improve the load transfer effect, and at the same time, weaken the galvanic corrosion behavior between the continuous fiber mesh and the matrix through the introduction of the corrosion inhibitor, thereby improving the overall corrosion resistance of the composite material;
[0008] Step 3, slicing the additive component: Slice the digital model of the additive component designed by the 3D modeling software in the height direction, with a slice thickness of 0.5 to 3.0 mm, and cut each layer of the continuous fiber mesh by laser cutting or wire electric discharge cutting according to the slice morphology;
[0009] Step 4: Matrix layer friction deposition forming: deposit a layer of metal matrix on the substrate or additively manufactured component. The basic device structure used for friction deposition includes three parts: a driving component, a set screw, and a constraint ring;
[0010] Step 5, laying the continuous fiber grid: laying the continuous fiber grid on the surface of the matrix additive manufacturing layer and rolling it flat;
[0011] Step 6, layer-by-layer additive manufacturing: repeat steps 4 and 5, and the sum of the thickness of each matrix manufacturing layer and the continuous fiber mesh is equal to the thickness of each layer of the additive component slice in step 3;
[0012] Step 7: Additive post-processing: Remove the additively manufactured component from the substrate by machining and perform fine processing according to product structure requirements.
[0013] Furthermore, the matrix of the metal matrix composite material is one of aluminum, aluminum alloy, magnesium, magnesium alloy, copper, copper alloy, titanium, and titanium alloy.
[0014] Furthermore, the degreasing step of cleaning the surface of the continuous fiber mesh is to immerse the continuous fiber mesh in a strong alkaline degreasing liquid at 70 to 90° C. for 10 to 60 minutes, and then rinse it with deionized water. The strong alkaline degreasing liquid is 100 g / L NaOH solution.
[0015] Furthermore, the pickling and weak etching steps for cleaning the surface of the continuous fiber mesh use a 10% HCl+5% HF mixed solution to clean and remove the surface oxide film and slightly corrode it to expose a fresh metal surface.
[0016] Furthermore, the surface texturing step of the continuous fiber mesh adopts 240g / L CrO3+2.4g / L H2SO4 (98%)+20.0g / L Na2MoO4 electrolyte, and the carbon plate is used as the anode and the continuous fiber mesh is used as the cathode for electrochemical texturing, and the electrolysis current density is 50-2000mA / cm 2 , a pulse duty cycle of 0.30-0.75, an electrolyte temperature of 40-90°C, and a duration of 10-120 min, are used to prepare a surface hairy layer with a high roughness on the surface of the continuous fiber mesh. At the same time, a corrosion inhibitor mainly composed of molybdate components is introduced to improve the mechanical interlocking of the interface while weakening the galvanic corrosion effect between the matrix and the continuous fiber mesh, thereby simultaneously improving the mechanical and corrosion resistance of the composite material.
[0017] The beneficial effects of the present invention are:
[0018] 1. The present invention proposes a friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite materials. Through the additive manufacturing idea of slicing and stacking layer by layer, it solves the bottleneck of the difficult manufacturing of complex structures of continuous fiber grid reinforced metal matrix composite materials;
[0019] 2. The friction deposition additive method used in the present invention is a pure solid phase process, which avoids the problem of excessive interface reaction in fused additive manufacturing. By combining electrochemical texturing and the introduction of corrosion inhibitors, the overall load-bearing performance and corrosion resistance of the composite material are significantly improved;
[0020] 3. The present invention is suitable for high-performance manufacturing of various continuous fiber grid-reinforced metal-based composite materials, and has a simple structure, low production cost and good feasibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of a friction deposition additive manufacturing method for a continuous fiber grid reinforced metal matrix composite material according to the present invention;
[0022] Figure 2 is a schematic diagram of a friction deposition additive manufacturing tool according to the present invention;
[0023] Figure 3 It is an isometric view of a continuous fiber grid reinforced metal matrix composite material according to the present invention;
[0024] Figure 4 is a front view of a semi-rigid constraint body in a round bar mode according to the present invention;
[0025] Figure 5 is a top view of a semi-rigid constraint body in a square bar mode according to the present invention;
[0026] Figures 1 to 5 In the figure, 1-continuous fiber grid reinforced metal matrix composite material, 101-matrix, 102-continuous fiber grid, 2-friction deposited rod-shaped raw material, 3-driving component, 301-mounting end, 30101-side fixed plane, 302-clamping end, 30201-clamping inner hole, 30202-setting screw hole, 4-setting screw, 5-constraint ring, 501-inner hole, 502-chamfer. DETAILED DESCRIPTION
[0027] Specific implementation method 1: Figures 1 to 5 As shown, a friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite material, the specific steps include:
[0028] Step 1, continuous fiber mesh surface cleaning: the surface of the continuous fiber mesh 102 is cleaned, including but not limited to degreasing, pickling and weak etching.
[0029] Step 2, surface roughening of the continuous fiber mesh: A pulse electrodeposition process is used to perform electrochemical roughening on the surface of the continuous fiber mesh 102 to produce a high-roughness surface structure and simultaneously introduce a corrosion inhibitor to strengthen the mechanical interlocking effect between the continuous fiber mesh 102 and the matrix 101 and improve the load transfer effect. At the same time, the galvanic corrosion behavior between the continuous fiber mesh 102 and the matrix 101 is weakened by the introduced corrosion inhibitor, thereby improving the overall corrosion resistance of the composite material 1.
[0030] Step 3, slicing the additive component: Slice the digital model entity of the additive component designed by the 3D modeling software in the height direction, with a slice thickness of 0.5 to 3.0 mm, and cut each layer of the continuous fiber mesh 102 by laser cutting or wire electric discharge cutting according to the slice morphology.
[0031] Step 4, friction deposition forming of the matrix layer: a layer of metal matrix 101 is deposited on the substrate or the additively manufactured component. The basic device structure used for friction deposition includes three parts: a driving component 3, a set screw 4, and a constraint ring 5. The driving component mounting end 301 is used to connect with the rotating spindle rotor part of machining equipment including but not limited to stir friction welding machines, CNC milling machines, CNC machining centers, etc., and is provided with a side fixed plane 30101 for side fixed clamping. A clamping inner hole 30201 is provided in the clamping end 302, which is used to clamp the friction deposited rod-shaped raw material 2, and its diameter is 0.05 to 0.20 mm larger than the friction deposited rod-shaped raw material 2, and is coaxially fixed and clamped by a set screw installed in the set screw hole 30202. The constraint ring 5 is a cylindrical ring structure, and the diameter of its inner hole 501 is 0.10 to 1.50 mm larger than that of the friction deposition rod-shaped raw material, and a chamfer 502 is provided at the upper end of the inner hole 501 to ensure that the friction deposition rod-shaped raw material 2 can easily pass through the inner hole 501 for friction deposition additive manufacturing, and its function is to suppress the problem of thermal plastic curling of the end surface of the deposited rod-shaped raw material 2 during the friction deposition process, which leads to a decrease in material utilization. The basic method is: the friction deposition rod-shaped raw material 2 rotates at high speed under the action of the high-speed rotating driving component 3, and passes through the constraint ring 5, and is thermally plasticized and deposited on the surface of the substrate or the additively manufactured component 1 under a certain axial force or downward pressure speed, forming a continuous additive manufacturing layer 101, and the thickness of the additive manufacturing layer can be controlled by the axial force or downward pressure speed.
[0032] Step 5: Laying the continuous fiber grid: Laying the continuous fiber grid 102 on the surface of the base additive manufacturing layer 101 and rolling it flat.
[0033] Step 6, layer-by-layer additive manufacturing: Repeat steps 4 and 5, and it should be noted that the sum of the thickness of each matrix manufacturing layer 101 and the continuous fiber mesh 102 should be equal to the thickness of each layer of the additive component slice in step 3. During the deposition process of each matrix additive manufacturing layer 101, due to the high-speed rotation friction heat plasticization and large plastic deformation of the end face of the friction deposited rod-shaped raw material 2, the matrix will penetrate into the continuous fiber mesh 102 in a hot plasticized solid state to produce mechanical interlocking, and form a metallurgical reaction with the interface of the continuous fiber mesh 102 to form a metallurgical bond.
[0034] Step 7: Additive post-processing: remove the additively manufactured component 1 from the substrate by machining, and perform fine processing according to product structure requirements.
[0035] The metal matrix composite material matrix 101 includes but is not limited to aluminum and aluminum alloys, magnesium and magnesium alloys, copper and copper alloys, titanium and titanium alloys, and the preferred materials include 5A06 deformation strengthened aluminum alloy, AZ31B magnesium alloy, and the like.
[0036] The strength of the material of the continuous fiber mesh 102 should be significantly higher than that of the matrix 101. For example, for an aluminum alloy matrix, TC4 titanium alloy, 2507 duplex stainless steel, tungsten-molybdenum alloy and the like can be preferably used.
[0037] Specific implementation method 2: Figures 1 to 5 As shown, the matrix of the metal matrix composite material is one of aluminum, aluminum alloy, magnesium, magnesium alloy, copper, copper alloy, titanium, and titanium alloy.
[0038] Specific implementation method three: Figures 1 to 5 As shown, the degreasing step for cleaning the surface of the continuous fiber mesh is to immerse the continuous fiber mesh in a strong alkaline degreasing liquid at 70 to 90° C. for 10 to 60 minutes, and then rinse it with deionized water. The strong alkaline degreasing liquid is 100 g / L NaOH solution.
[0039] Specific implementation method four: Figures 1 to 5 As shown, the pickling and weak etching steps for cleaning the surface of the continuous fiber mesh use a 10% HCl+5% HF mixed solution to clean and remove the surface oxide film and slightly corrode it to expose a fresh metal surface.
[0040] Specific implementation method five: Figures 1 to 5 As shown, the continuous fiber mesh surface texturing step uses 240g / L CrO3+2.4g / L H2SO4 (98%)+20.0g / L Na2MoO4 electrolyte, with the carbon plate as the anode and the continuous fiber mesh as the cathode for electrochemical texturing, and the electrolysis current density is 50-2000mA / cm 2 , a pulse duty cycle of 0.30-0.75, an electrolyte temperature of 40-90°C, and a duration of 10-120 min, are used to prepare a surface hairy layer with a high roughness on the surface of the continuous fiber mesh. At the same time, a corrosion inhibitor mainly composed of molybdate components is introduced to improve the mechanical interlocking of the interface while weakening the galvanic corrosion effect between the matrix and the continuous fiber mesh, thereby simultaneously improving the mechanical and corrosion resistance of the composite material.
[0041] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent replacement and improvement made to the above embodiments without departing from the content of the technical solution of the present invention, based on the technical essence of the present invention, within the spirit and principles of the present invention, still fall within the protection scope of the technical solution of the present invention.
Claims
1. A friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite materials, characterized in that: Specifically include: Step 1, continuous fiber mesh surface cleaning: cleaning the continuous fiber mesh surface, including degreasing, pickling and weak etching; Step 2, continuous fiber mesh surface texturing: The surface of the continuous fiber mesh is electrochemically texturized by a pulse electrodeposition process to produce a high-roughness surface structure and simultaneously introduce a corrosion inhibitor to strengthen the mechanical interlocking effect between the continuous fiber mesh and the matrix, improve the load transfer effect, and at the same time, weaken the galvanic corrosion behavior between the continuous fiber mesh and the matrix through the introduction of the corrosion inhibitor, thereby improving the overall corrosion resistance of the composite material; Step 3, slicing the additive component: Slice the digital model of the additive component designed by the 3D modeling software in the height direction, with a slice thickness of 0.5 to 3.0 mm, and cut each layer of the continuous fiber mesh by laser cutting or wire electric discharge cutting according to the slice morphology; Step 4: Matrix layer friction deposition forming: deposit a layer of metal matrix on the substrate or additively manufactured component. The basic device structure used for friction deposition includes three parts: a driving component, a set screw, and a constraint ring; Step 5, laying the continuous fiber grid: laying the continuous fiber grid on the surface of the matrix additive manufacturing layer and rolling it flat; Step 6, layer-by-layer additive manufacturing: repeat steps 4 and 5, and the sum of the thickness of each matrix manufacturing layer and the continuous fiber mesh is equal to the thickness of each layer of the additive component slice in step 3; Step 7: Additive post-processing: Remove the additively manufactured component from the substrate by machining and perform fine processing according to product structure requirements.
2. The friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite material according to claim 1, characterized in that: The matrix of the metal matrix composite material is one of aluminum, aluminum alloy, magnesium, magnesium alloy, copper, copper alloy, titanium and titanium alloy.
3. The friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite material according to claim 1, characterized in that: The degreasing step for cleaning the surface of the continuous fiber mesh is to immerse the continuous fiber mesh in a strong alkaline degreasing liquid at 70 to 90° C. for 10 to 60 minutes, and then rinse it with deionized water. The strong alkaline degreasing liquid is 100 g / L NaOH solution.
4. The friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite material according to claim 1, characterized in that: The pickling and weak etching steps for cleaning the surface of the continuous fiber mesh use a 10% HCl+5% HF mixed solution to clean and remove the surface oxide film and slightly corrode it to expose a fresh metal surface.
5. The friction deposition additive manufacturing method for continuous fiber grid reinforced metal matrix composite material according to claim 1, characterized in that: The continuous fiber mesh surface roughening step uses 240g / L CrO3+2.4g / L H2SO4(98%)+20.0g / LNa2MoO4 electrolyte, with the carbon plate as the anode and the continuous fiber mesh as the cathode for electrochemical roughening, and the electrolysis current density is 50~2000mA / cm 2 , a pulse duty cycle of 0.30-0.75, an electrolyte temperature of 40-90°C, and a duration of 10-120 min, are used to prepare a surface hairy layer with a high roughness on the surface of the continuous fiber mesh. At the same time, a corrosion inhibitor mainly composed of molybdate components is introduced to improve the mechanical interlocking of the interface while weakening the galvanic corrosion effect between the matrix and the continuous fiber mesh, thereby simultaneously improving the mechanical and corrosion resistance of the composite material.
Citation Information
Patent Citations
Systems and methods for controlling additive manufacturing
CN109906136A
Metal component forming method
CN116408610A
Continuous fiber composite material adding device and method based on laser melting stirring friction technology
CN117507414A
Method for manufacturing metal-based composite material based on friction stir additive
CN117754108A
Three dimensional printing
US20140291886A1